Hubungan Komunikasi Interpersonal Terhadap Kerjasama Tim Pada Divisi Produksi Di PT.X - Sugiyo, Michael Alyarow Kurnia; Rahayu, Puspita Puji (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
The aim of this research is to examine the extent of interpersonal communication relationships with collaborative teams in the production division at PT. X. The respondents in this research were production employees with a population of 120 people, while the respondents used were 35 respondents. The measuring instrument used in this research is a Likert scale including the Teamwork Scale and Interpersonal Communication Scale. The data was then analyzed statistically using product moment analysis from Pearson. The results of the analysis showed that the correlation coefficient (r) between interpersonal communication and team collaboration was 0.306 with p (one-tailed) = 0.000 (p<0.05). Shows that there is a significant relationship between interpersonal communication and team collaboration. Another result obtained was the determinant coefficient (R- Squared) of 0.828. which means that interpersonal communication has an effective contribution to team collaboration of 82.8%, while 17.2% is influenced by other factors.